Supervision of The Implementation of UKL-UPL in Medium-Risk Business Licensing based on The Risk-Based Licensing System - Virda Rachma Mulya; Nunik Nurhayati (Universitas Muhammadiyah Surakarta, 2026)
The transformation of the licensing paradigm in Indonesia from a permit-based system (license-based) into risk-based business licensing through the enactment of Law Number 6 of 2023 and Government Regulation Number 28 of 2025 has brought fundamental implications for environmental protection instruments, especially for medium-risk business activities that use UKL-UPL documents. In line with the perspective of human trust as khalifah fil ard in preserving the earth, integrating ecological values into economic regulations is essential to prevent environmental damage. This normative legal research applies a legislative and conceptual approach with qualitative analysis, aiming to evaluate the effectiveness of supervision of business actors' compliance within the latest regulatory framework that tends to emphasize investment facilitation. The novelty of this research lies in a critical analysis of the problems of post-permit supervision mechanisms integrated into the system. Online Single Submission Risk-Based Approach (OSS-RBA), a crucial dimension for environmental legal certainty which has not been explored in depth. The results of the study indicate that the integration of UKL-UPL into the Business Identification Number or Standard Certificate has created a supervisory transformation that encompasses administrative aspects through periodic report evaluations and substantive aspects through field inspections. However, the findings indicate a disconnect between theoretical norms and practical reality due to the ambiguity of sanction parameters, the limited number of Environmental Supervisory Officers (PPLH) compared to business volume, and the dominance of independent reports with minimal physical verification. Therefore, this study concludes that the current legal system is unable to guarantee legal certainty or optimal protection of ecosystem functions. Strengthening institutional capacity and strict synchronization of operational data are needed to ensure that the UKL-UPL instrument is not degraded into a mere administrative formality for the sake of pursuing investment legality alone.